PENERAPAN PEMBATASAN SOSIAL BERSKALA BESAR (PSBB) AKIBAT PANDEMI CORONAVIRUS DISEASE 2019 (COVID-19) SEBAGAI FORCE MAJEURE DALAM KONTRAK [Implementation of Large-scale Social Restrictions due to Coronavirus Disease-19 (Covid-19) Pandemic as Force Majeure in Contract] - Velliana Tanaya; Jessica Angeline Zai (Fakultas Hukum, Universitas Pelita Harapan | Lippo Karawaci, Tangerang, 2021)
A contract is an agreement made by the parties in written form. An agreement is a binding agreement between two or more people. This incident resulted in a legal relationship between the parties, which in the agreement included the rights and obligations of each party. In a contract, there is always a force majeure clause, the arrangements are made to protect the debtor when carrying out his obligations there has been an unexpected event beyond his fault. Since the end of 2019 until now the spread of Covid-19 has been very widespread and has had an impact on slowing economic growth, resulting in the fulfillment of contract achievements executed by the parties. This article was made to examine the classification of force majeure in contracts in connection with the widespread spread of Covid-19 which resulted in the contract relationship not going well, but it was not automatically used as an excuse to cancel a contract. The research method used is normative legal research with a legal and conceptual approach. The result of the research is that the force majeure clause can be an attempt to restructure or change the contents of the agreement while taking into account the agreement of the parties through the negotiation process. The concept of force majeure in the context of non-natural disasters as regulated in Presidential Decree No. 12 of 2020, which is the discharge of responsibility and the release of fulfillment of one party's achievements for a while or is called relative force majeure. The parties' discretion is needed to carry out business contract negotiations such as rearranging the fulfillment of achievements as stated in the contract.Bahasa Indonesia Abstrak: Sebuah perjanjian adalah persetujuan yang dibuat oleh para pihak dalam bentuk tertulis. Perjanjian tersebut kemudian mengikat dua pihak atau lebih. Hal ini menimbulkan hubungan hukum di antara para pihak, di mana di dalamnya terdapat hak dan kewajiban masing-masing pihak. Dalam sebuah perjanjian akan selalu ada klausul force majeure, yang ditujukan utnuk melindungi debitur jika pada saat melaksanakan kewajibannya terdapat kejadian di luar kesalahannya. Sejak akhir tahun 2019 hingga sekarang, penyebaran Covid-19 semakin meluas dan berdampak pada kelesuan pertumbuhan ekonomi, dan pemenuhan kewajiban dalam perjanjian oleh para pihak. Artikel ini bertujuan meneliti klasifikasi force majeure dalam kontrak dalam hubungannya dengan penyebaran Covid-19 yang berdampak pada hubungan kontraktual menjadi tidak lancar, namun tidak otomatis membatalkan perjanjian tersebut. Metode penelitian yang digunakan ialah penelitian hukum normatif dengan pendekatan undang-undang dan konseptual. Hasil dari penelitian ialah klausul force majeure dapat menjadi upaya untuk merestuktur atau mengubah isi perjanjian dengan tetap memperhitungkan kesepakatan para pihak melalui proses negosiasi. Konsep force majeure dalam konteks bencana non-alam yang diatur dalam Keputusan Presiden No. 12 Tahun 2020, melepaskan tanggung jawab pemenuhan perjanjian untuk sementara waktu, atau yang disebut dengan force majeure relatif. Keputusan para pihak dibutuhkan dalam bernegosiasi untuk melangsungkan pemenuhan prestasi yang diatur dalam perjanjian.